Domači vrabec Passer domesticus - Grošelj, Peter (Acrocephalus, 1998)
Colony of 20 nests in 1995 on a cedar tree at petrol station near Koper
Keywords: domači vrabec; House Sparrow; Koper; opazovanje; ornithology; ornitologija; Slovenia